Asymptotic analysis of Sturm-Liouville problem with Dirichlet and nonlocal two-point boundary conditions - Štikonas, Artūras; Şen, Erdoğan (Mathematical Modelling and Analysis, 2023)
In this study, we obtain asymptotic expansions for eigenvalues and eigenfunctions of the one–dimensional Sturm–Liouville equation with one classical Dirichlet type boundary condition and two-point nonlocal boundary condition. We analyze the characteristic equation of the boundary value problem for eigenvalues and derive asymptotic expansions of arbitrary order. We apply the obtained results to the problem with two-point nonlocal boundary condition.